KEWENANGAN PEMERINTAH PROVINSI BALI DALAM PEMBERIAN HIBAH KEPADA DESA PAKRAMAN - Gde Agus Erry Sukresna Arna (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2016)
Bali Provincial Government has allocated financial aid specifically for indigenous village (Pakraman) in Bali. In addition to the government's budget also allocates the budget grants to indigenous village (Pakraman). The budget allocated for the fulfilment of development and societal. Terms of the grant is contained in Law No. 23 in 2014 on particular especially Article 298 paragraph (5). Post-enactment of Law No. 23 in 2014 avoid confusion which led to the grant that had been awarded to indigenous village (Pakraman) in Bali could not be implemented because it must refer to the provisions of Article 298 paragraph (5) letter d that the grant can only be given to the agency , institutions, and civil society organizations under the Indonesian law. To overcome confusion about the Government grant recipient object in this case Ministry of Home Affairs issued Regulation of the Minister of the Interior of the Republic of Indonesia Number 14 in 2016 concerning the Second Amendment to the Regulation of the Minister of Interior of the Republic of Indonesia Number 32 in 2011 on Guidelines for Grant and the Social Assistance That Sourced From Revenue and Expenditure budget of Regions. This rule is used as a guideline in giving grants to indigenous village (Pakraman). Departing from this, there are two problems, namely how the substance of the Bali Provincial Government Authority in awarding grants to indigenous village (Pakraman) and how grants ideal setting to indigenous village (Pakraman). This research was conducted with the use of normative legal research conducted through an analysis of the norms of the legislation. The approach in this study using the approach of legislation, analytical approach legal concepts and approaches of history. Legal materials used in this research is the primary legal materials, secondary law and tertiary legal materials. Based on the results obtained that the Bali Provincial Government has set Regulation of Bali Governor No. 29 in 2016 on Guidelines for Grants and Social Assistance. The authority of the Governor in provide grants accordance with regional capabilities to supporting the achievement of program objectives and activities of local government based on the urgency and regional interests in supporting the implementation of the functions of government and community development with regard to the principle of justice, decency, rationality, and benefits to society. While setting the grant that ideal for indigenous village (Pakraman) order to avoid mistakes is to revise Law No. 23 in 2014 on Regional Government, especially with the adding clauses customary law community unit in grant recipient object that does not cause multiple interpretations.Pemerintah Provinsi Bali telah mengalokasikan bantuan keuangan khusus bagi desa pakraman di bali. Selain anggaran tersebut pemerintah juga mengalokasikan anggaran hibah kepada desa pakraman. Anggaran tersebut diperuntukkan untuk pemenuhan pembangunan dan kemasyarakatan. Ketentuan pemberian hibah termuat pada Undang-Undang Nomor 23 Tahun 2014 khususnya pada Pasal 298 ayat (5). Pasca ditetapkannya  Undang-Undang Nomor 23 Tahun 2014 terjadi kesimpangsiuran yang meyebabkan pemberian dana hibah yang selama ini diberikan kepada desa pakraman di bali tidak bisa dilaksanakan karena harus mengacu pada ketentuan pasal 298 ayat (5) huruf d bahwa pemberian dana hibah hanya dapat diberikan kepada badan, lembaga, dan organisasi kemasyarakatan yang berbadan hukum Indonesia. Untuk mengatasi kesimpangsiuran tentang objek penerima dana hibah Pemerintah dalam hal ini Kementerian Dalam Negeri mengeluarkan Peraturan Menteri Dalam Negeri Republik Indonesia Nomor 14  Tahun 2016 tentang Perubahan Kedua Atas Peraturan Menteri Dalam Negeri  Republik Indonesia Nomor 32 Tahun 2011 Tentang Pedoman Pemberian Hibah Dan Bantuan Sosial Yang Bersumber Dari Anggaran Pendapatan Dan Belanja Daerah. Peraturan inilah dipergunakan sebagai pedoman dalam memberikan hibah kepada desa pakraman. Bertolak dari hal tersebut, substansi permasalahannya ada dua yaitu bagaimanakah Kewenangan Pemerintah Provinsi Bali dalam pemberian hibah kepada Desa Pakraman serta bagaimanakah pengaturan pemberian hibah yang ideal kepada Desa Pakraman. Penelitian ini dilaksanakan dengan menggunakan penelitian hukum normatif yang dilakukan melalui analisis terhadap norma dalam peraturan perundang-undangan. Pendekatan dalam penelitian ini menggunakan pendekatan perundang-undangan, pendekatan analisis konsep hukum serta pendekatan sejarah. Bahan hukum yang digunakan dalam penelitian ini adalah bahan hukum primer, bahan hukum sekunder serta bahan hukum tersier. Berdasarkan hasil penelitian didapat bahwa Pemerintah Provinsi Bali telah menetapkan Peraturan Gubernur Bali Nomor 29 Tahun 2016 tentang Pedoman Pemberian Hibah dan Bantuan Sosial. Kewenangan Gubernur dalam memberikan hibah sesuai dengan kemampuan daerah guna menunjang pencapaian sasaran program dan kegiatan pemerintah daerah berdasarkan urgensi dan kepentingan daerah dalam mendukung terselenggaranya fungsi pemerintahan, pembangunan dan kemasyarakatan dengan memperhatikan asas keadilan, kepatutan, rasionalitas, dan manfaat untuk masyarakat. Sedangkan pengaturan pemberian hibah yang ideal untuk desa pakraman agar tidak terjadi kekeliruan adalah merevisi Undang-Undang Nomor 23 Tahun 2014 tentang Pemerintahan Daerah khususnya dengan penambahan klausul kesatuan masyarakat hukum adat dalam objek penerima hibah agar tidak menimbulkan multitafsir.